For as defined above, find .
Notations :
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It suffices to evaluate ∫ 0 n ⌊ x ⌋ d x to get an answer.
∫ 0 n ⌊ x ⌋ d x = r = 0 ∑ n − 1 ∫ r r + 1 r d x = r = 0 ∑ n − 1 r = 2 n ( n − 1 )
Exploiting the property { x } = x − ⌊ x ⌋ it can be easily derived that the ratio is n − 1
So it follows that n = 1 ∑ n ( n − 1 ) = 2 n 2 − n